Up = Yukarı bak - Docter, Pete ([S.l.] : Disney-Pixar, 2009)
Carl Fredricksen spent his entire life dreaming of exploring the globe and experiencing life to its fullest. But at age 78, life seems to have passed him by, until a twist of fate (and a persistent 8-year old Junior Wilderness Explorer named Russell) gives him a new lease on life.
Region 2.
K-3.
Language : Turkish, English, German.
Subtitle : Turkish, English, German.
Keywords: Movie -- animated films; Movie -- Kids/Family.